Stability and performance evaluation of the speed control of DC motor using state-feedback controller - Saad A. Salman; Zeyad Assi Obaid; Haider Salim Hameed (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Direct current (DC) motor are widely used in many applications due to its accurate control of speed and position. However, a proper control and operation is still required and might be a challenge for control designers. This paper presents the design of a state-feedback control to evaluate the performance of the speed control of DC motor for different applications. The simulation results were carried out with and without disturbance applied to the system. The proposed control method showed a stable system response with both cases of disturbances. Therefore, it can be used to solidate the control of DC motor in the real application.